Les adaptations médiatiques des archives en médiation scientifique : étude du scénario sémiotique « tourisme montagnard transfrontalier » - Marie-Hélène Hermand (Revue de Géographie Alpine)
Following an approach inspired by Foucault’s archaeology of knowledge, and in line with contemporary research into the semantic modelling of discourse, I observe how the use of archives by scientific communication frames our perceptions and representations of mountains. The study corpus consists of various online scientific communication devices (websites, exhibition, webinar, documentary, conference and game) consisting of situated examples from two contexts (the Dolomites and the High Atlas). The objective is to analyse the construction and adaptations of the “transfrontier mountain tourism” semiotic scenario. By drawing on the concepts of topos, scenario and argument I am able to describe the ways in which this scenario is adapted into different media, and to identify its tourism and transfrontier components, which are made explicit to varying degrees. In the process, the results formally presented in conceptual graphs supply a provisional semio-pragmatic model for describing and interpreting the transfrontier universe of discourse.